A Record Based Study on Pediatric Tuberculosis in Ahmedabad City, India - Bhavna Puwar; Vaibhavi Patel; Tapasvi Puwar (Medsci Publications, 2012)
Backdround: Good data on the burden of all forms of TB amongst children in India are scarce. There is an urgent need to study the available data. Methodology: This record based study was conducted in Ahmedabad city situated in western region of India. Five treatment units out of total ten units were selected by random sampling method. Records of Paediatric TB patients registered between February 2007 and January2008 were studied. Results: Out of total 382 records studied 193 (50.5%) were girls and 189 (49.5%) were boys with mean age of 8.3 years. Forty six percent of cases were in category III. Fifty four percent cases were of Extra- Pulmonary TB (EPTB). Total 123 patients who missed the doses, only one third were paid home visit. Eighty three percent of the children completed their treatment and 6% cases were declared as cured. Five children died during treatment. Conclusions: Analysis of records suggests high treatment completion rate amongst RNTCP paediatric TB patients in Ahmedabad city. It also suggests scope of improvement in home visits paid to patients who miss the doses during the treatment.